Farmers perception and awareness about agriculture insurance scheme – a study of north karnataka - Rao, N Maruti (Journal of Management and Science, 2021)
Agriculture is considered the backbone of Indian economy. The agriculture sector determines the growth and sustainability of Indian economy. About 52% of India’s workforce and 21% of India’s population still relies on agriculture for employment and livelihood. In spite of this, 197 farmers had committed suicide in 2015 in Karnataka (till September) and North-Karnataka accounted for 25 percent of such suicide cases compared to an average of 15 percent in remaining 5 regions of Karnataka (as per political map of Karnataka). As per the officials from agriculture department, none of the farmers who committed suicide had taken a crop insurance policy. These lives might have been saved if the crop is insured against climate change. As per the records of Agriculture Insurance Company of India (AIC) Ltd, only 16.3 percent of all farmers in Karnataka are covered under the NAIS. In the light of this observation, the researcher felt that it is high time to assess the awareness and existing knowledge about crop insurance among farmers. It is also necessary to assess perception of farmers about crop insurance. The study reveals that farmers have lot of faith in Pradhan Mantri Fasal Bima Yojana. They have strong confidence in PMFBY that it will provide security against Crop Loss. However, they opined that there is no provision in the policy for risk coverage of both Kharif and Rabi Seasons. It is suggested that crop insurance should be delivered along with crop loan through banks. The agriculture department (GOK) should conduct an awareness programme in collaboration with Management Educational Institutes. This will not only help in creation of awareness but also educating farmers about crop insurance